COMMUNITY STRUCTURE OF SEA URCHIN AS AN INDICATOR OF THE ECOLOGICAL BALANCE OF COASTAL AREAS - Radjab, Abdul Wahab; Rabiyanti, Intan; Muharby, Fiqih (UI Scholars Hub, 2023)
Sea urchins, soft-shelled invertebrates (Echinoderms), crucially contribute to cleaning the ocean bottom. However, sea urchins in tropical waters like Indonesia have not yet been fully disclosed. This study was conducted at Hutumuri and Rutong waters, Ambon City. This study assessed physical-chemical parameters, sea urchin species composition, classification, and community structure. Employing the Line Transect method with 5x5 m quadrants and 50m transect spacing, data analysis included density, relative density, frequency of presence, diversity, uniformity, and dominance indices. Results indicated normal temperature and salinity at both stations, supporting sea urchin life, with rocky and sandy substrates deemed suitable. A total of 1,772 sea urchins were identified, led by Echinometra mathaei and lowest in Echinothrix calamaris. Classifying sea urchins revealed four species from three families: Echinometridae (Echinometra mathaei), Toxopneustidae (Tripneustes gratilla), and Diadeimatidae (Echinothrix calamaris and Diadema antillarium). Echinometra mathaei dominated Station 2 with 879 individuals, while Echinothrix calamaris was least abundant at Station 1, Echinometra mathaei density peaked at Station 1, while Echinothrix calamaris had the lowest at Station 2. Station 1 showed the highest diversity, Station 2 exhibited the highest uniformity, and Station 1 had the highest dominance. These findings offer insights for sustainable marine resource management in the studied area.